2016
DOI: 10.1038/nsmb.3321
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale ATP-independent nucleosome unfolding by a histone chaperone

Abstract: DNA accessibility to regulatory proteins is significantly affected by nucleosome structure and dynamics. FACT (facilitates chromatin transcription) increases the accessibility of nucleosomal DNA but the mechanism and extent of this nucleosome reorganization are unknown. We report here the effects of FACT on single nucleosomes revealed with spFRET microscopy. FACT binding results in a dramatic, ATP-independent, and reversible uncoiling of DNA that affects at least 70% of the DNA in a nucleosome. A mutated versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
143
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(169 citation statements)
references
References 53 publications
11
143
0
7
Order By: Relevance
“…Subsequent analyses demonstrated that FACT is a histone chaperone responsible for disassembly and reassembly of nucleosomes during transcription and DNA replication [74,75]. More recent single molecule FRET studies show that FACT binds to mono-nucleosomes and can induce partial uncoiling of nucleosomal DNA from histones, consistent with a role for FACT in activating transcription elongation through chromatinized DNA templates [76]. Structural studies on the FACT complex show that it is composed of four distinct domains: Spt16 N-terminal domain (Figure 4A), the dimerization domains of Spt16 and SSRP1, the middle domains of Spt16 and SSRP1 (Figures 4B and 4C, respectively), and the long C-terminal domains (CTD) of Spt16 and SSRP1, which are predicted to be disordered and have acidic stretches (Figure 3) [7779].…”
Section: Introductionmentioning
confidence: 95%
“…Subsequent analyses demonstrated that FACT is a histone chaperone responsible for disassembly and reassembly of nucleosomes during transcription and DNA replication [74,75]. More recent single molecule FRET studies show that FACT binds to mono-nucleosomes and can induce partial uncoiling of nucleosomal DNA from histones, consistent with a role for FACT in activating transcription elongation through chromatinized DNA templates [76]. Structural studies on the FACT complex show that it is composed of four distinct domains: Spt16 N-terminal domain (Figure 4A), the dimerization domains of Spt16 and SSRP1, the middle domains of Spt16 and SSRP1 (Figures 4B and 4C, respectively), and the long C-terminal domains (CTD) of Spt16 and SSRP1, which are predicted to be disordered and have acidic stretches (Figure 3) [7779].…”
Section: Introductionmentioning
confidence: 95%
“…However, it should be noted that multiple studies have shown that FACT can disrupt nucleosome structure in vitro (X in et al . 2009; V alieva et al . 2016), and thus we cannot rule out the possibility that FACT further alters chromatin structure once bound.…”
Section: Discussionmentioning
confidence: 99%
“…Second, unique characteristics of H2A.X-F (e.g., its extended, acidic carboxyl terminus) could weaken or destabilize interactions between histones and DNA, consequently facilitating the productive action of topo II and/or condensin I on nucleosome arrays. A similar argument may also be applied to the action of the histone chaperone FACT, as recent structural studies suggested that FACT facilitates nucleosome reorganization by partially disrupting histone-DNA interactions (Hondele et al 2013;Kemble et al 2015;Tsunaka et al 2016;Valieva et al 2016). It is therefore reasonable to speculate that FACT confers structural flexibility on nucleosomes in the chromatid reconstitution reaction.…”
Section: Nucleosome Dynamics During Chromatid Assemblymentioning
confidence: 99%